2002
DOI: 10.1002/glia.10061
|View full text |Cite
|
Sign up to set email alerts
|

Expression of glial fibrillary acidic protein and glutamine synthetase by Müller cells after optic nerve damage and intravitreal application of brain‐derived neurotrophic factor

Abstract: Müller glia play an important role in maintaining retinal homeostasis, and brain-derived neurotrophic factor (BDNF) has proven to be an effective retinal ganglion cell (RGC) neuroprotectant following optic nerve injury. The goal of these studies was to investigate the relation between optic nerve injury and Müller cell activation, and to determine the extent to which BDNF affects the injury response of Müller cells. Using immunocytochemistry and Western blot analysis, temporal changes in the expression of glia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 54 publications
0
70
0
Order By: Relevance
“…7 A,C(ii)). GFAP is known to be expressed in Müller glia and astrocytes (Chen and Weber 2002). GFAP was found co-localized with GS in the Müller glial endfeet ( Fig.…”
Section: Macrogliamentioning
confidence: 89%
See 1 more Smart Citation
“…7 A,C(ii)). GFAP is known to be expressed in Müller glia and astrocytes (Chen and Weber 2002). GFAP was found co-localized with GS in the Müller glial endfeet ( Fig.…”
Section: Macrogliamentioning
confidence: 89%
“…It has already been shown that an upregulation of cytoskeletal proteins and downregulation of GS is associated with activated porcine Müller glia in culture (Hauck et al, 2003). In addition, decreased levels of GS in the Müller glial somata were observed following optic nerve crush (Chen and Weber 2002), which was interpreted as Müller glia initiating dedifferentiation in an attempt to replace dying cells. A reduction in GS could be additive to the already stressful environment in the rd10, as GS is known to be neuroprotective against retinal insult (Gorovits et al, 1997).…”
Section: Macrogliamentioning
confidence: 94%
“…In contrast, a change in glutamine synthetase expression appears to depend on the type of retinal damage that is sustained , with glutamine synthetase levels decreasing in response to photoreceptor cell damage and increasing under conditions of hepatic retinopathy. In the case of either diabetic retinopathy or optic nerve crush, there is no significant change in the levels of glutamine synthetase (Mizutani et al, 1998;Chen and Weber, 2002).…”
Section: Ouabain Damage Fails To Cause the Müller Glia To Exhibit Reamentioning
confidence: 99%
“…As a general measure of glial reactivity, we examined immunolabeling intensity of the astrocyte marker GFAP and the Müller glia marker glutamine synthetase. An increase in the expression of these markers is associated with increased reactivity or activation of astrocytes and Müller glia in response to a variety of stressors in retina [37][38][39][40][41][42][43][44]. Since we evaluated overall labeling intensity, increases in GFAP or glutamine synthetase levels can be attributed to either increased expression on a per cell basis, which accompanies hypertrophy, or an increase in density.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that uptake and anterograde transport of CTB by RGCs is an early indicator of RGC decline [34][35][36]. Similarly, expression of GFAP by astrocytes and glutamine synthetase by Müller cells is altered in response to retinal damage, including glaucoma [37][38][39][40][41][42][43][44]. For our analysis in whole mount retina, we sampled 60x fields in the area between mid-central and mid-peripheral retina.…”
Section: Stressor-dependent Changes In Gp130 Are Accompanied By Altermentioning
confidence: 99%